Chemokines, their receptors and human disease: the good, the bad and the itchy. Issue 4 (1st April 2015) - Bryant, Vanessa L; Slade, Charlotte A
Abstract : Chemokines are a highly specialized group of cytokines that coordinate trafficking and homing of leucocytes between bone marrow, lymphoid organs and sites of infection or inflammation. They are also responsible for structural organization within lymphoid organs. Aberrant expression or function of these molecules, or their receptors, has been linked to protection or susceptibility to specific infectious diseases, as well as the risk of autoimmune disease and malignancy, revealing critical roles of chemokines and their receptors in human health, disease and therapeutics. In this review, we focus on human diseases that provide lessons regarding the critical role of these specialized and complex cytokines. Abstract : The April 2015 issue contains a Special Feature on "Chemokines in cellular positioning and human disease". Chemokines serve as critical extracellular mediators of cell migration and retention. Recent studies have highlighted the importance of how cells are positioned within peripheral and lymphoid tissues for the development of timely effector and memory responses. In addition, advances in structural determination of chemokine receptor‐ligand complexes and the identification of genetic mutations that impact cell migration have brought us closer to targeting this system for the development of new anti‐inflammatory and anti‐tumor based drugs. Immunology and Cell Biology thanks the coordinator of this Special Feature ‐ Joanna Groom ‐ for her planning and input.